Adapting in the Knowledge Economy: Lateral Strategies for Scientists and Those Who Study Them - Birgitte Gorm Hansen (Copenhagen Business School (CBS), 2011)
The thesis Adapting in the Knowledge Economy investigates the strategies deployed by academic scientists when trying to adapt and maneuver within an increasingly complex mixture of scientific, industrial and governmental agendas. Chapter one “From insights to invoice” summarizes the last decade of Danish research policy as a tendency towards intensified focus on interaction between the university and “outside” actors. Looking at Danish policy documents and interview data the chapter shows how policy changes responded to an idea of “ivory tower” researchers isolating themselves in Danish universities. Furthermore, the interaction agenda was motivated by the perception that knowledge was produced but not sufficiently used. Strongly influenced by the concept of the knowledge economy and that of mode 2 knowledge production, policy changes were directed at bridging a gap between the producers and the consumers of knowledge. A series of reforms and initiatives were launched to facilitate more interaction between science and industry as well as more responsiveness towards societies' problems on behalf of the universities. This interaction agenda was coupled with an increase in the economic investment in research and an increased focus on competition between researchers in order to ensure high quality in knowledge production....
hdl:10398/8346
Keywords: 650